1999
DOI: 10.1038/20338
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic pollen harms monarch larvae

Abstract: have reported a preference for heavy women with high waist-to-hip ratios (WHR) in a culturally isolated population in southeast Peru. Their findings are interesting because a preference for low WHR is widespread in westernized populations 2-5 . However, we disagree with their argument that cultural invariance is necessary for an adaptionist interpretation of WHR preference.WHR and waist circumference are positively correlated with testosterone and negatively associated with oestrogen 6 . Women with low WHR hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
455
1
29

Year Published

2000
2000
2009
2009

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 970 publications
(485 citation statements)
references
References 1 publication
0
455
1
29
Order By: Relevance
“…Of particular interest are beneficial insects such as pollinators (Picard-Nizou et al, 1995;Arpaia, 1996;Poppy, 1998;Malone et al, 2001) and natural enemies of pests (Hilbeck et al, 1998;Birch et al, 1999;Bell et al, 2001), but the effects on non-target Lepidoptera has also received much attention (Losey et al, 1999;Jesse & Obrycki, 2000;Wraight et al, 2000;Zangerl et al, 2001). The debate on how to conduct these assessments has not yet been settled, but it is commonly accepted that realistic tests should compare conventional methods with the strategy of employing transgenic plants, although this is rarely done as yet.…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest are beneficial insects such as pollinators (Picard-Nizou et al, 1995;Arpaia, 1996;Poppy, 1998;Malone et al, 2001) and natural enemies of pests (Hilbeck et al, 1998;Birch et al, 1999;Bell et al, 2001), but the effects on non-target Lepidoptera has also received much attention (Losey et al, 1999;Jesse & Obrycki, 2000;Wraight et al, 2000;Zangerl et al, 2001). The debate on how to conduct these assessments has not yet been settled, but it is commonly accepted that realistic tests should compare conventional methods with the strategy of employing transgenic plants, although this is rarely done as yet.…”
Section: Introductionmentioning
confidence: 99%
“…The results suggested that pollen from the most widely planted Bt-maize events (MON810 and Bt 11) will have no acute effects on larvae in field settings [62,63] since their pollen expresses 80 times less toxin than Event 176 [63]. The results also suggested that pollen densities used by Losey et al [61] were in excess compared to pollen densities present in maize fields or that the pollen of event Bt 11 used may have been contaminated with non-pollen tissues [64]. Excessive pollen densities of the currently commercialized events (Bt 11 and MON810) would be required to obtain relevant adverse effects on larval developments [62].…”
Section: Effects Of Bt-crops On Butterfliesmentioning
confidence: 87%
“…The case of Bt-maize pollen and the monarch butterfly (Danaus plexippus) caused much public interest and led to a debate over the potential risks and the environmental impact of Bt-maize. Losey et al [61] found that when pollen from a commercial variety of Bt-maize (event Bt 11) was spread on milkweed leaves in the laboratory and fed to monarch butterfly larvae, the larvae consumed significantly less from these leaves compared with leaves dusted with non-transgenic pollen. In addition, after 4 days, almost half of the tested larvae died, which was significantly more than on the leaves with non-transgenic pollen where none of the tested larvae died.…”
Section: Effects Of Bt-crops On Butterfliesmentioning
confidence: 99%
“…The publication by Losey et al (1999) showing that Monarch larvae are sensitive to Bt maize pollen, which can be regarded as a typical Tier 1 study, was at the origin of a major controversy that could probably have been avoided. That Monarch larvae could be harmed by Bt maize pollen was not surprising, since Cry1Ab is toxic to many Lepidoptera, but in the absence in 1999 of exposure data from the field, it was impossible at the time to determine the actual risk to the populations of Monarchs.…”
Section: Box 2 the Monarch Butterfly Controversy Seen In Retrospectmentioning
confidence: 99%